The Parliamentary privileges and conventions in Malaysia / Zahari Kechik - Kechik, Zahari (Faculty of Law, 1985)
The nature of our Parliamentary privilege in Malaysia is derived from the provision of Clause (1) Article 63 of the Federal Constitution; "The validity of any proceedings in either House of Parliament or any Committee thereof shall not be questioned in any Court‘. The position as regard to the nature of this privilege in Malaysia is mutatis-mutandis the position in England, Parliamentary privilege has been defined as; 'the sum of peculiar right enjoyed by each House collectively as a constituent part of the High Court of Parliament, and by members of each House individually without which they could not discharge their function, and which exceed those possessed by other bodies or individuals'. As the chief legislative organ in the country Parliament should exercise certain powers and privilege which are regarded as essential to the dignity and proper functioning of it. Every member of the Houses of Parliament, therefore, must be free to carry out his responsibilities without inhibition.